Analisis Minat Dan Kepuasan Anggota Koperasi Simpan Pinjam Dan Pembiayaan Syariah Di Wilayah Bungatan Situbondo - Ahmad Muzayyin; Muhammad Irfan; Moh. Lailul Ilham; Firdiana (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This study aims to analyze the factors that influence the interest in becoming a member and the level of satisfaction of members of BMT NU Bungatan Branch. The research method used is qualitative method. Data collection is done through observation, interviews and documentation. The results showed that location, profit sharing, promotion, and trust factors had a significant effect on interest in becoming a member of BMT. The most popular savings product is Tabah while the most popular financing product is Al-Qardhul Hasan. The level of member satisfaction with BMT services reaches 100%, this is due to the friendly and polite attitude of employees, responsiveness in handling complaints, and compatibility between expectations and realization of financing. In conclusion, BMT NU Bungatan Branch needs to improve marketing strategies and maintain service quality to increase member interest and satisfaction.